Aplikasi Perangkat Mobile untuk Layanan Tamu di Hotel Gold Inn, Sampit - Hendry Cahyadi; Henry Novianus Palit; Kristo Radion Purba (Jurnal Infra, 2018)
Gold Inn Hotel, located in the city of Sampit, Central Kalimantan, was established on July 27, 2007. Nowadays many new hotels are popping up in the city of Sampit, making the competition in the hospitality business more and more tight. Therefore all hotels are racing to provide the best services in order to become the main choice of potential customers. All Gold Inn Hotel's competitors still use the phone to place orders. Staying guests should use the phone to make all reservations. Frequently, it takes a long time for the guest to place an order. In addition, morning call requests and taxi orders to the airport are often misplaced and not executed because they are still done manually (generally using paper).Mobile Device Application for Guest Services at Gold Inn Hotel, Sampit is aimed to assist hotel guests in making reservations, so as to improve services at Gold Inn Hotel.